Assessing People’s Willingness to Participate in Counter Violent Extremism Programmes: The development of Counterradicalism Readiness Scale (CoRS) - Zora A. Sukabdi (Kuras Institute, 2022)
Counterterrorism approach in Indonesia emphasizes on prevention rather than prosecution. Radicalism could lead to the acts of terrorism; hence, in terms of terrorism prevention, the role of civil society is significant in avoiding radicalization of people. Here lies the urgency of community empowerment. As an instrument to examine people’s readiness in preventing terrorism is unclear, this study was held. The study intends to formulate an instrument for measuring counterradicalism readiness (called ‘CoRS’). It aimed to evaluate people’s readiness to be involved in counterradicalism and CVE (Counter Violent Extremism) programs. The development of CoRS was organized into detailed steps: 1) defining counterradicalism readiness and its aspects, 2) identifying behaviour indicators of counterradicalism readiness, 3) making items for scale, 4) performing items’ readability test, 5) conducting pilot study, and 6) holding statistical analysis. Quantitative method was applied in this study by involving 19 security practitioners to assess CoRS’ content-related validity and 227 participants for the instrument’s reliability (with Alpha Cronbach and Omega McDonnald). The findings demonstrate the efficacy of CoRS’ items in measuring counterradicalism readiness. Furtmermore, CoRS reaches satisfactory reliability α=0.92 and ω=0.93. The study may assist practitioners in identifying people’s readiness and willingness to participate in counterradicalism programs.